Superperc: Minimally-Invasive Percutaneous Nephrolithotomy Initial Experience - Bhuiyan, N I; Islam, Md Hasibul; Rana, Md Masud; Al Mamun, Md Abdullah; Arafat, M Ali (Bangladesh Journal of Urology, 2023)
Introduction: For the management of renal stones, Percutaneous nephrolithotomy (PCNL) has undergone significant changes in the last few years in the quest for improving efficacy and reducing morbidity. Minimally-invasive modalities of PCNL, such as mini- PCNL, ultra-mini PCNL, and micro-PCNL, have evolved with advancements in optics and technology. However, with these newer advancements, the migration of small fragments produced with laser lithotripsy remains a concern, which may result in incomplete stone clearance. A new technique of PCNL is termed “Superperc” that utilizes suction to remove all the fragments and maintain a one-way flow. Methods: This study involved 35 consecutive patients who underwent PCNL with the Superperc technique from March 2020 to December 2020. Surgery was performed using a pediatric ureteroscope used as a nephroscope and a specially designed sheath with a suction attachment. The Superperc uses a 10/12 F tract size, a specially designed Superperc sheath (Shah Sheath) with a suction mechanism, and a pediatric ureteroscope 4.5/6. Results: The age range is 20-65 years, with 23 males and 12 females. Stone size was 1- 3 cm, and operative time was 30-90 min. Upper calyceal punctures 7cases , 19 had middle, 6 lower calyceal and 3 had two punctures. DJ stent was placed in 7 patients, whereas 28 patients had a ureteric catheter for 24 hours. Only three patients required a nephrostomy tube. No blood transfusion. Postoperatively one patient had a mild fever, and one had transient hematuria. Complete stone clearance as per nephroscopy &fluoroscopy. The hospital stay was 24-72 h. Conclusion: Superperc is a new technique of minimally-invasive PCNL and can be successfully done with minimal modification in the armamentarium, with the potential advantage of good stone clearance. Bangladesh J. Urol. 2022; 25(2): 71-75